IMPLEMENTASI PEMBELAJARAN TATAP MUKA DIMASA PANDEMI COVID-19 DI MAN 2 LAMONGAN - Eli Kurniasari; Tjitjik Rahaju (Universitas Negeri Surabaya, 2022)
During the pandemic, the policies of the education industry are constantly changing, what was originally done with face-to-face freedom has evolved from distance learning (PJJ) to limited face-to-face learning (PTM). During the limited PTM implementation, there are 2 learning systems of 50% capacity and 100% capacity, this is adjusted to the regional conditions of each region at the PPKM level. The limited implementation of PTM at MAN 2 Lamongan has shown a difference in the perception of teachers, students and parents about policy acceptance. This presents advantages and disadvantages as well as challenges and obstacles in the implementation of limited CTP. The purpose of the study was to know how to implement PTM at MAN 2 Lamongan during the pandemic and the preparation of schools to implement PTM during the pandemic. The study used descriptive method. The data collection process is obtained through interviews, observations and documentation. The data was processed using Milles and Huberman's analytical techniques including data reduction, data presentation, and drawing conclusions. The objective of this study used four indicators according to George Edward III, including communication, resources, staffing and structure. The results show that a face-to-face learning implementation can work well even if it frequently undergoes policy changes, and there are facilities to support PTM implementation during the pandemic. The challenge encountered when implementing PTM is the undisciplined attitude of the implementer. Meanwhile, the obstacles teachers and students face are related to the short learning time. Keywords: Policy Implementation, Face-to-face Learning, Covid-19